Information System Audit in a Spare Parts Distribution Company Using the ITIL V3 Service Strategy Framework - Francka Sakti Lee; Yunianto Purnomo; Honni; Christian Kurniadi Jusuf; Samuel Winata; Steven Saputra (Journal of Information System and Informatics, 2026)
Information system audits play an important role in evaluating the effectiveness, governance, and strategic alignment of IT services within organizations. This study assesses the capability level of IT service strategy implementation in a spare-parts distribution company using the ITIL V3 framework, with a focus on three Service Strategy sub-processes: Service Portfolio Management, Financial Management, and Demand Management. A qualitative case study approach was employed through semi-structured interviews and document analysis involving key personnel responsible for IT service operations. Capability assessment used a binary scoring method, where Fully Achieved was rated as 1 and Not Achieved as 0, and the aggregated results were mapped to capability levels. The findings show that the organization operates between Level 2 (repeatable) and Level 3 (defined), indicating that core processes have been documented and partially implemented, but are not yet fully integrated across functions. Key gaps were identified in internal coordination, management information, monitoring practices, and customer interface mechanisms. The study recommends strengthening service governance through clearer policies, better cross-functional coordination, and more integrated monitoring to improve IT service performance and business alignment.